Interpreting Southeast Asia's Past : Monument, Image and Text - Pigott, Vincent C.; Guy, John, 1949-; Sharrock, Peter D.; Glover, Ian, 1934-; Bacus, Elisabeth A. (Book collections on Project MUSE., 2013)
'Interpreting Southeast Asia's Past: Monument, Image and Text' contains 31 papers read at the 10th International Conference of the European Association of Southeast Asian Archaeologists. The authors present new research on monumental arts, sculpture and painting, epigraphy and heritage management across mainland Southeast Asia and as far south as Indonesia. New monumental arts research includes papers focused on the enduring enigma of the Bayon of Angkor, as well as material on the great brick temple sites of the state of Champa, neighbors of the ancient Khmers. The sacred art of Burma, Thailand and southern China incites new analysis of sculpture and painting including the first study of the few surviving Saiva images in Burma. The collection includes an account of a spectacular find of bronze Mahayana Buddhas, an analysis of the sculpted bronzes of the Dian culture, and an assessment of the purpose of making and erecting sacred sculptures in the ancient world. Ancient Khmer materials, including recently discovered Cambodian ceramic kiln sites, are the main focus of new research on craft goods and crafting techniques that treat the source, dating and adoption of amalgam gilding among Khmer craft specialists; the sandstone sources of major Khmer sculptures; and the rare remaining traces of paint, plaster and stucco on Khmer stone and brick buildings. More widely distributed goods also receive attention, including Southeast Asian glass beads. There are also contributions to Southeast Asian heritage and conservation, including research on Angkor as a living World Heritage site, and discussion of a UNESCO project on the stone jars of the Plain of Jars in Laos that combines recording, safeguarding, bomb clearance, and eco-tourism development.